Implementasi Inovasi “Baraka” untuk Kewirausahaan Penyandang Disabilitas - Dessy Kurniasari; Donard Games; Berri Brilliant Albar; Ares Albirru Amsal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
People with disability can have difficulties in expressing their talents and capabilities, including in entrepreneurship. They also may have limited resources and a lack of opportunity to access information and knowledge. For these reasons, we introduce “Baraka” as an online learning platform for entrepreneurship designed to assist people with disabilities, including students, by providing videos and information that enhance their knowledge and skills. Innovation implementation requires some elements such as financial resources availability, top management team support, innovation climate, and human resources availability. Baraka also needs to focus on people with disability ’aspirations to make sure that they can benefit from this platform and proactively participate to become a source of knowledge and skills. It is also essential for having continuous improvement and total support from stakeholders for this project.